REVIEW OF CONTEXT AND COMMUNICATION CONTENT IN SECONDARY TRADITIONAL COMMUNITIES SECONDARY VILLAGE - Ardiyansyah Ardiyansyah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The phenomenon of the demands of an increasingly modern and increasingly advanced era makes Remote Indigenous Communities known as the Suku Anak Dalam inevitably have to be involved in various communication contexts. This study aims to determine the form or context of communication that takes place in Remote Indigenous Communities, and see the content or elements of messages in building communication during the social interaction of Suku Anak Dalam in the midst of the life of the majority of Malay people in Saramangun, Sekamis Village, Jambi. This study was analyzed using the concept of the context of communication contexts with the Qualitative Method. describe and analyze the phenomena and social activities of the Anak Dalam Tribe. Data was collected through in-depth interviews in the Anak Dalam community, structured field observations and documentation. The data analysis technique used is that according to Matthew B. Miles and A. Michael Huberman (in Sugiyono, 2012: 246) there are three components, namely: Data Reduction, Data Presentation and Verification / Withdrawal of Conclusions. Field findings and analysis results show that the context and content of Communication in Remote Indigenous Communities is using Interpersonal Communication, Group Communication, Organizational Communication.